Response of iron and zinc on vegetative and reproductive growth of strawberry (Fragaria × Ananassa Duch.) cv. Chandler - Singh, Manjit; Jamwal, Mahital; Sharma, Nirmal; Kumar, Rajesh; Wali, VK (Bangladesh Journal of Botany, 2018)
Foliar application of 0.2% FeSO4 + 0.3% ZnSO4 thrice at monthly interval tended to exhibit the highest plant height and spread, number of leaves per plant, average leaf area, number of flowers, fruits, marketable fruits per plant and total yield and marketable yield per plant. These plants also took the least duration to attain the age of flowering as well as harvesting.